Genetic regulation of TERT splicing affects cancer risk by altering cellular longevity and replicative potential - Florez-Vargas, Oscar; Ho, Michelle; Hogshead, Maxwell H.; Papenberg, Brenen W.; Lee, Chia-Han; Forsythe, Kaitlin; Jones, Kristine; Luo, Wen; Teshome, Kedest; Blauwendraat, Cornelis; Billingsley, Kimberley J.; Kolmogorov, Mikhail; et al. (Nature communications, 2025)
The chromosome 5p15.33 region, which encodes telomerase reverse transcriptase (TERT), harbors multiple germline variants identified by genome-wide association studies (GWAS) as risk for some cancers but protective for others. Here, we characterize a variable number tandem repeat within TERT intron 6, VNTR6-1 (38-bp repeat unit), and detect a strong link between VNTR6-1 alleles (Short: 24-27 repeats, Long: 40.5-66.5 repeats) and GWAS signals rs2242652 and rs10069690 within TERT intron 4. Bioinformatics analyses reveal that rs10069690-T allele increases intron 4 retention while VNTR6-1-Long allele expands a polymorphic G-quadruplex (G4, 35-113 copies) within intron 6, with both variants contributing to variable TERT expression through alternative splicing and nonsense-mediated decay. In two cell lines, CRISPR/Cas9 deletion of VNTR6-1 increases the ratio of TERT- full-length (FL) to the alternative TERT-β isoform, promoting apoptosis and reducing cell proliferation. In contrast, treatment with G4-stabilizing ligands shifts splicing from TERT-FL to TERT-β isoform, implicating VNTR6-1 as a splicing switch. We associate the functional variants VNTR6-1, rs10069690, and their haplotypes with multi-cancer risk and age-related telomere shortening. By regulating TERT splicing, these variants may contribute to fine-tuning cellular longevity and replicative potential in the context of stress due to tissue-specific endogenous and exogenous exposures, thereby influencing the cancer risk conferred by this locus. Several multi-cancer GWAS loci within the region encoding telomerase reverse transcriptase (TERT) have been identified. Here, the authors explore the locus within TERT intron 4, link it with a variable number tandem repeat (VNTR), and investigate its biological significance and role in cancer.